Research progress of ferroptosis in acute kidney injury - Zhang, Lin; Luo, Feng; Yuan, Nan; Yin, Jiaming; Shen, Bing; Chai, Yalin; Sun, Lijie; Wang, Xuan; Yin, Le; Luo, Congjuan (Frontiers in Cell and Developmental Biology, 2025)
Acute kidney injury (AKI) is a life-threatening condition characterized by a rapid decline in kidney function caused by various underlying factors. Despite advancements in medical science, effective treatments for AKI remain limited, highlighting the necessity for novel therapeutic strategies. Ferroptosis, an iron-dependent regulated cell death characterized by lipid peroxidation, has been recently linked to AKI development. Studies indicate that ferroptosis plays a role in multiple AKI types, such as those caused by ischemia-reperfusion, sepsis, nephrotoxic agents, and rhabdomyolysis. In these conditions, ferroptosis markers are elevated in renal tubular epithelial cells, and inhibiting ferroptosis has been shown to reduce kidney injury. However, the precise regulatory mechanisms of ferroptosis in AKI remain unclear. This review summarizes current understanding of ferroptosis, including its definition, molecular regulation, involvement in various AKI types, and potential therapeutic targets. By elucidating these aspects, we hope to provide a foundation for future research and the development of effective interventions for AKI.